Tambo Alam Pauh Duo dan Surambi Sungai Pagu sebagai Panduan dalam Penetapan Nagari di Kabupaten Solok Selatan, Sumatera Barat - Putra, Agil Angriyansyah (YASIN, 2025)
Tambo plays a crucial role in the governance system of nagari in West Sumatra; however, modernization and government policies have influenced its sustainability. This study aims to analyze the role of Tambo Alam Pauh Duo and Surambi Sungai Pagu in the establishment of nagari in Solok Selatan Regency and the factors affecting their continuity. Using a qualitative approach with historical ethnographic methods, this research involves in-depth interviews with traditional leaders, community figures, and local government representatives, as well as an analysis of historical documents and relevant regulations. The findings reveal that tambo serves four primary functions: as a marker of cultural identity, a basis for territorial legitimacy, a governance guideline for nagari administration, and a tool for social harmonization. Community participation, customary documentation, government regulations, and globalization play significant roles in shaping the sustainability of the nagari governance system. The main challenges identified include the impact of modernization, which shifts the role of customary traditions in governance, and the weakening of customary documentation, threatening the continuity of traditional values. Therefore, a collaborative effort between indigenous communities and the government is essential to maintaining a balance between tradition and contemporary changes. The digitization of tambo and the strengthening of regulations that accommodate customary values are strategic steps to ensure the relevance and sustainability of nagari governance in the future.